The Influence of Leadership Style, Work Discipline, and Work Supervision on Employee Work Effectiveness in The General Division of the Regional Secretariat Office of The Cirebon District Government - Trimayanti, Imas; DWI YANTHI, WINDA; Herlina, Ellin; Fawaiz, Rohmatul; Warsuna, Warsuna (Jurnal Ekuisci, 2024)
Effectiveness denotes the extent to which management operations successfully achieve predetermined objectives. The profitability and sustainability of a firm are largely dependent on the efficiency of its workforce. Therefore, ensuring that the organization's resources function as efficiently as possible is essential. Factors affecting employee productivity include leadership style, job discipline, and supervision. This study aims to evaluate the influence of leadership style, work discipline, and work supervision on employee effectiveness at the Cirebon Regency Regional Secretariat Office in the General Section. This research was conducted at the General Section of the Cirebon Regency Regional Secretariat office. This research is categorized as causal associative research utilizing a quantitative methodology, signifying that the entire population serves as the sample for the study. The employed data sources consist of primary and secondary data, utilizing data collection methods such as questionnaires, observation, and documentation. Data analysis methodologies encompass instrument evaluation (validity and reliability assessments), descriptive percentage analysis, classical assumption verification, multiple regression analysis, and hypothesis testing utilizing SPSS for Windows version 22.0. The study results indicate that the three independent variables have a significantly positive effect on the dependent variable. The results suggest that the t count for all variables exceeds the t table value of 2.051, demonstrating a significant effect of variable X1 on variable Y at 4.085, variable X2 on variable Y at 4.014, and variable X3 on variable Y at 3.310, with a significance level of α = 5% (p < 0.05). Additionally, the findings of the hypothesis test yielded a value of 35.532, which exceeds 2.975. The R Square value of 0.804 indicates that Leadership Style (X1), Work Discipline (X2), and Work Supervision (X3) account for 80.4% of the variance in Employee Performance (Y). The remaining 19.6% is influenced by unassessed variables. The R-value indicates a strong correlation between the three independent factors and the dependent variable in this study.